Evaluation of Fire Safety Performance Towards Sustainable Design iof Gombe State University Senate Building - Sabo, L; El-Nafaty, A. S.; Bashir, U. M.; Adamu, I.U.; Kawuwa, S. A.; Umar, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Fire safety in architectural design is a critical concern globally, particularly in educational institutions due to their high occupancy rates. This study evaluates the fire safety performance of Gombe State University’s Senate Building, identifying gaps in existing fire safety measures and proposing sustainable solutions. A mixed-methods approach was employed, integrating literature reviews, case studies, stakeholder interviews, questionnaires, and fire safety simulations. Key deficiencies identified include obsolete fire alarm systems, insufficient sprinkler coverage, poor visibility of exit signage, and lack of emergency lighting. The study recommends an integrated fire safety framework incorporating advanced fire prevention technologies and sustainable architectural solutions to enhance safety standards in educational buildings.